Influence of the racket on the smash motion in badminton - Kawano, T.; Takehara, S.; Kasamatsu, S.; Suzuki, K. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to analyze the influence of the racket on badminton smash motion. An experiment was carried out using three badminton rackets of different mass and gravity center position. The smashes of 12 males were selected for the analysis. Performances were recorded by twelve motion capture cameras. In this study, we analyzed a position in the vertical direction of each marker and considered a series of the flow of the smash motion. Then, we calculated the standard deviation to analyze a difference of the smash motion. As a result, a difference in dispersion of the smash motion was observed depending on using the rackets. In addition, some inexperience persons could be close to motions of experience by changing the rackets. Therefore, the result showed that it was very important to select a racket suitable for them.